Selfishness, warfare, and economics; or integration, cooperation, and biology - Salvucci, Emiliano J. (Frontiers in Cellular and Infection Microbiology, 2012)
The acceptance of Darwin's theory of evolution by natural selection is not complete and it has been pointed out its limitation to explain the complex processes that constitute the transformation of species. The darwinian paradigm had its origin in the free market theories and concepts of Malthus and Spencer. Nature was explained on the basis of market theories moving away from an accurate explanation of natural phenomena. It is common that new discoveries bring about contradictions that are intended to be overcome by adjusting results to the dominant reductionist paradigm using all sorts of gradations and combinations that are admitted for each case. Modern findings represent a challenge to the interpretation of the observations with the Darwinian view of competition and struggle for life as theoretical basis. New holistic interpretations are emerging related with the Net of Life, in which the interconnection of ecosystems constitutes a dynamic and self-regulating biosphere: Viruses are recognized as a macroorganism with a huge collection of genes, most unknown, that constitute the major planet's gene pool with a fundamental role in evolution. The hologenome theory considers an organism and all of its associated symbiotic microbes as a result of symbiopoiesis. Microbes, helmints, that normally are understood as parasites, are cohabitants and they have cohabited with their host and drives the evolution and existence of the partners. Each organism is a result of integration of complex systems. The eukaryotic organism is the result of combination of bacterial, virus and eukaryotic DNA and the interaction of its own genome with the genome of its microbiota resulting in an intertwined metabolism (a “superorganism”) along evolution. These new interpretations are remarkable points to be considered in order to construct a solid theory adjusted to the facts and with less speculations and tortuous semantic traps.